Chair’s Summary: Mechanisms of Exacerbation of Lung Diseases - Nicod, Laurent P. (Ann Am Thorac Soc, 2015)
This year’s conference focused on the origins of exacerbations in chronic lung diseases, such as asthma, chronic obstructive pulmonary disease, idiopathic pulmonary fibrosis, and cystic fibrosis. Common themes emerged, with the role of viral infections being key. In addition, there were data presented supporting the role of the microbiota and microbial dysbiosis either in the gut or in the lung contributing to disease progression and the susceptibility to disease exacerbation. These effects can be amplified by the triggering of biologic cascades that include alterations in oxidative stress and inflammatory mediator release, which can be driven by epithelial cell injury or activation.